Deep into the dark eaudiobook A mystery. - Tracy, P. J. (Detective Margaret Nolan, 2021)
New York Times bestseller P. J. Tracy returns with Deep into the Dark , a brand new series set in LA and featuring up-and-coming LAPD Detective Margaret Nolan and murder suspect Sam Easton. Sam Easton — a true survivor — is home from Afghanistan, trying to rebuild a life in his hometown of LA. Separated from his wife, bartending and therapy sessions are what occupy his days and nights. When friend and colleague Melody Traeger is beaten by her boyfriend, she turns to Sam for help. When the boyfriend turns up dead the next day, a hard case like Sam is the perfect suspect. But LAPD Detective Margaret Nolan, whose brother recently died serving overseas, is sympathetic to Sam's troubles, and can't quite see him as a killer. She's more interested in the secrets Melody might be keeping and the developments in another murder case on the other side of town. Set in an LA where real people live and work—not the superficial LA of Beverly Hills or the gritty underbelly of the city— Deep into the Dark features two really engaging, dynamic main characters and explores the nature of obsession, revenge, and grief. P. J. Tracy is known for her "fast, fresh, and funny" characters (Harlan Coben) and her "sizzling" plots ( People ); the Monkeewrench series was her first, set in Minneapolis and co-written with her mother. Now with Deep into the Dark she's on her own — and it's a home run. A Macmillan Audio production from Minotaur Books